S126. THE RELATION OF THE PSYCHOSIS CONTINUUM WITH SCHIZOPHRENIA POLYGENIC RISK SCORE AND CANNABIS USE. (18th May 2020) - Quattrone, Diego; Ferraro, Laura; Tripoli, Giada; Rodriguez, Victoria; Marino, Paolo; Vassos, Evangelos; Morgan, Craig; Reininghaus, Ulrich; Lewis, Cathryn; Murray, Robin; Di Forti, Marta
Abstract: Background: There has been much debate about whether research into psychosis should be conducted using symptom dimensions as opposed to diagnostic categories. Indeed, dimensions, like categories, may be practical but arbitrary tools for research and clinical practice; hence, they should not be based on psychometric data only. The aim of this study was to externally validate empirically derived symptom dimensions using combined genetic and environmental data. Specifically, we examined the hypothesis that the continuous multivariate distribution of psychosis is a function of cannabis use and genetic liability to schizophrenia, as summarised by polygenic risk score (SZ-PRS). Methods: As part of the European Network of National Schizophrenia Networks Studying Gene-Environment Interactions (EU-GEI) study, we analysed a large multinational sample of First Episode Psychosis patients (FEP) and population controls, with available genotype and psychopathology information. Using item response modelling in Mplus, we estimated a bifactor model of psychotic symptoms in FEP, and of psychotic experiences in controls. Using PRSice, we built SZ-PRS by weighting individuals' risk variants by the log(odds ratio), where the odds ratio was extracted from the latest summary statistics of Psychiatric Genomic Consortium mega-analyses on schizophrenia. Finally, we used linear regression to test the combined associations of the positive symptom/experience dimensions with SZ-PRS and daily/current cannabis use, separately in FEP and controls, after covarying for 10 ancestry principal components, sex, age, and primary diagnosis. Results: The continuous distribution of psychosis was represented by two bi-factor models composed of 1) in FEP, one general psychosis factor and five specific dimensions; 2) in controls, one general psychosis factor and three specific dimensions. Linear regression modelling showed that in 617 FEP, both daily cannabis use (B=0.31; 95%CI 0.11 to 0.52; p=0.002) and SZ-PRS (B=0.22; 95%CI 0.04 to 0.39; p=0.014) were independently associated with the dimension of positive symptoms. Similar results were found in 979 population controls, with a positive association of both current use of cannabis (B=0.26, 95%CI 0.06 to 0.46; p=0.011) and SZ-PRS (B=0.13, 95%CI 0.02 to 0.25; p=0.022) with the dimension of psychotic experiences. Discussion: We found two factors associated with the latent dimensional structure of psychosis. SZ risk variants and cannabis use independently map onto specific dimensions of positive symptoms, contributing to variation across the psychosis continuum. Our study supports the theory that psychotic experiences in the general population are biologically similar to clinical psychotic symptoms.